BATASAN PELAKSANAAN HAK INGKAR NOTARIS DALAM RANGKA MENJAGA KERAHASIAAN AKTA MENURUT UNDANG -UNDANG REPUBLIK INDONESIA NOMOR 2 TAHUN 2014 PERUBAHAN UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS - ammanda michelle sumampow; Mella Ismelina F.R. (Jurnal Hukum Adigama, 2021)
Notary is a public official who is guided by UUJN which thus gives the Notary full authority to make a Deed, along with the obligation to keep the contents of the Deed, as in the Notary’s commitment to his oath or promise. Thus the Deed made by the Notary is confidential and the entire process of maintaining it is a confidentiality legal protection effort. However, the fact that a Notary can be summoned to make inquiries and become a witness in a court permitted by law presents a dilemma in itself with the promise of Notary it should. To overcome this dilemma, the Notary is facilitated with a right called dissenters rights, which then gives the option for the Notary to deny his position as a witness in certain circumstances. Considering this, the author would like to see the implementation of the dissenters rights according to UUJN and also the limitations of the confidentiality of the Deed that the author will be conducted with normative juridical research using a statue approach, as well as using secondary data from books and scientific writings relevant to the dissenters rights of notary and confidentiality of the Deed. After conducting research, the authors identified that in the of dissenters rights of refusal of a Notary as an obligation stated in the law attached to his or her job duties, it has not been carried out clearly due the provision of Article 66 paragraph (1) UUJN which weakens the confidentiality of Deeds and dissenters rights.